2002
DOI: 10.1002/dvdy.10070
|View full text |Cite
|
Sign up to set email alerts
|

Cell–matrix interactions during development and apoptosis of the mouse mammary gland in vivo

Abstract: Epithelial cell survival is dependent on extracellular signals provided by both soluble factors and by adhesion. In the mammary gland, extensive apoptosis of epithelial cells occurs rapidly when lactation ceases, but the mechanism of apoptosis induction is not known. In tissue culture, mammary epithelial cells require laminin as a survival ligand and specific ␤1 integrins are necessary to suppress apoptosis. To explore the possibility that dynamic changes in cell-matrix interactions contribute to the onset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 77 publications
4
57
0
Order By: Relevance
“…This implies that the function of β1 integrin is required for the correct initiation of involution. On the other hand, it has been reported that the level of ligand-bound β1 integrin declined when apoptosis of mammary epithelial cells began during involution (38). From all these observations, we speculate that the fall of ligand-bound β1 integrin levels leads to the drop in clusterin expression at day 3 of involution.…”
Section: Discussionsupporting
confidence: 52%
“…This implies that the function of β1 integrin is required for the correct initiation of involution. On the other hand, it has been reported that the level of ligand-bound β1 integrin declined when apoptosis of mammary epithelial cells began during involution (38). From all these observations, we speculate that the fall of ligand-bound β1 integrin levels leads to the drop in clusterin expression at day 3 of involution.…”
Section: Discussionsupporting
confidence: 52%
“…Degradation of nuclear DNA into fragments that form ladders on agarose gels, apoptotic morphology of epithelial cells exhibiting chromatin condensation, and activation of effector caspases, all characteristic markers of apoptosis, are observed within 2 d of withdrawing pups. 48,[50][51][52][53] Apoptotic mammary epithelial cells must be cleared immediately by phagocytes in involuting mammary glands to prevent inflammation and autoimmune response against intracellular antigens released by the dying cells. Phagocytosis of apoptotic mammary epithelial cells by both macrophages and residual living epithelial cells has been demonstrated with convincing data, and three potential fates of apoptotic mammary epithelial cells have been suggested: release into the lumen, and phagocytosis by neighboring alveolar epithelial cells or macrophages.…”
Section: )mentioning
confidence: 99%
“…27 Recent work, however, tends to show that the earliest events of apoptosis occur before detectable changes in extracellular matrix or cognate integrin receptors can be detected. 28 Other survival signals of importance are the insulin-like growth factors (IGFs), whose function can be blocked by IGF-binding proteins (IGFBP). For example, IGFBP-5 is produced very early at the onset of involution; hence, it could well be a relevant mediator of apoptosis in mammary involution.…”
Section: Discussionmentioning
confidence: 99%